A pure acrylic glue

By using components such as acrylic copolymers and epoxy resins in acrylate pure adhesives and using aluminum diethylphosphinate as a new flame retardant filler, the synthesis problems of high molecular weight acrylic copolymers and the problems of cohesion oscillation are solved, and the effects of high flame retardancy, heat resistance and adhesive stability are achieved.

CN118755413BActive Publication Date: 2025-04-08SHANGHAI RAILI ELECTRONIC MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410819082.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-24
Publication Date
2025-04-08
Estimated Expiration
2044-06-24

AI Technical Summary

Technical Problem

The existing high molecular weight acrylic copolymers are difficult to achieve high conversion during the synthesis process, and there are prone to small molecules residues, resulting in a decrease in heat resistance of the adhesive, and excessive molecular weight leads to cohesion shock, affecting the stability of the adhesive.

Method used

Acrylic copolymer A, epoxy resin B, C, curing agent D, crosslinking agent E and new flame retardant filler F, especially aluminum diethylphosphinate as new flame retardant filler, improve cohesive oscillation through complexation reaction with acrylic copolymer, and provide good flame retardant performance and heat resistance.

Benefits of technology

It improves the cohesive stability of acrylate pure adhesive, enhances its flame retardant performance, reaches 94VTM-0 level, and improves the stability of heat resistance and adhesive force.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004908604990000051
    Figure BDA0004908604990000051
  • Figure BDA0004908604990000061
    Figure BDA0004908604990000061
  • Figure BDA0004908604990000062
    Figure BDA0004908604990000062
Patent Text Reader

Abstract

The present invention relates to the technical field of polymer compounds, and in particular to an acrylic pure glue. The acrylic pure glue is prepared from raw materials including: acrylic copolymer A, epoxy resin B, epoxy resin C, epoxy resin curing agent D, crosslinking agent E, and novel flame retardant filler F; the average particle size of the novel flame retardant filler F is 3 to 10 μm. The flame retardancy of the prepared acrylic pure glue can reach UL94V‑0 level, which can improve the material synthesis difficulty of acrylic pure glue adhesives, reduce the weight average molecular weight of acrylic copolymers without changing the bonding strength, reduce energy consumption, save costs, and at the same time improve the cohesive force oscillation of acrylic pure glue adhesives and improve the stability of bonding performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer compounds, in particular to pure acrylic glue. Background Art

[0002] In order to ensure a high level of flame retardancy, adhesives used in electronic materials such as semiconductor sealing materials and epoxy-based copper-clad laminates include bromine-containing epoxy resins, etc. However, since compounds containing halogens such as bromine release toxic gases when burned, the use of halogen-free materials in adhesives has been intensively studied in recent years.

[0003] Chinese patent application No. 200510107143.3 discloses an acrylic adhesive composition and an acrylic adhesive sheet, which are prepared from acrylic polymer, fusible phenolic resin, epoxy resin, non-polar filler, etc. and have excellent heat resistance and storage stability.

[0004] However, high molecular weight acrylic copolymers, such as acrylic copolymers with a weight average molecular weight of 500,000 to 700,000, are difficult to synthesize under normal conditions, and the conversion rate is low. It is easy to have small molecular residues, which leads to reduced heat resistance of pure adhesives. Moreover, when the molecular weight is too high, the greater the difference in molecular weight of each molecule, the greater the difference in the intermolecular force of each molecule. When the acrylic copolymer reacts with epoxy resin to prepare an adhesive, the adhesive is prone to cohesive force oscillation, which is manifested as a wave shape on the peel strength test interface. Summary of the invention

[0005] In order to solve the problems in the prior art, the present invention provides an acrylic ester pure glue, the preparation raw materials of which include: acrylic copolymer A, epoxy resin B, epoxy resin C, epoxy resin curing agent D, crosslinking agent E, and new flame retardant filler F; the average particle size of the new flame retardant filler F is 3 to 10 μm.

[0006] Preferably, the novel flame retardant filler F is a phosphorus-containing flame retardant complex having an average particle size of 3 to 10 μm.

[0007] Furthermore, the phosphorus-containing flame retardant complex is aluminum diethylphosphinate.

[0008] Furthermore, the model of the aluminum diethylphosphinate is Exolit OP 935, purchased from Clariant.

[0009] The applicant has found that, firstly, aluminum diethylphosphinate can react with acrylic copolymer to form a complex reaction, so that the connection of acrylic copolymer is tighter, thereby improving the cohesive oscillation of pure glue adhesive and improving the stability of bonding force; secondly, the phosphorus-containing aluminum diethylphosphinate complex can provide good flame retardant properties and is halogen-free, so that the flame retardancy of pure glue adhesive can reach 94VTM-0 level; thirdly, the decomposition temperature of the aluminum diethylphosphinate complex is 380°C or above, which can improve the heat resistance of pure glue adhesive; fourthly, the average particle size of the aluminum diethylphosphinate complex is 3 to 10 μm, which can promote its uniform dispersion and dissolution in the system. If the particle size is too large, it is difficult to dissolve and cannot be fully mixed; if the particle size is too small, the cost is too high, and it is easy to agglomerate in the system, making it difficult to disperse and dissolve.

[0010] Preferably, the raw materials of the acrylic copolymer A include, by weight, 30-50% of acrylic acid ester monomer a, 10-30% of acrylic acid ester monomer b, 10-30% of acrylonitrile monomer c, and 1-10% of acrylic acid ester monomer d.

[0011] Furthermore, the raw materials of the acrylic copolymer A include, by weight percentage, 30-50% of acrylate monomer a without epoxy group, 10-30% of acrylate monomer b without epoxy group, 10-30% of acrylonitrile monomer c, and 1-10% of acrylate monomer d containing epoxy group.

[0012] Furthermore, the weight percentage of the acrylate monomer a not containing epoxy groups is preferably 40-50%; the weight percentage of the acrylate monomer b not containing epoxy groups is preferably 20-30%.

[0013] The applicant has found that when the amount of the epoxy-free acrylate monomer a and the epoxy-free acrylate monomer b in the acrylic copolymer A is too small, the flexibility of the finally prepared acrylic pure glue adhesive is reduced and the bonding strength is poor; if the amount of both is too much, the heat resistance of the pure glue adhesive is reduced.

[0014] Preferably, the mass percentage of the acrylonitrile monomer c is 20-30%; the mass percentage of the epoxy-containing acrylate monomer d is 4-6%.

[0015] When the amount of acrylonitrile monomer c and epoxy-containing acrylate monomer d in the acrylic copolymer A is too small, the heat resistance of the acrylic pure glue adhesive will be reduced. When the amount is too large, the flexibility will be reduced, and it will be difficult to dissolve in the solvent, making the synthesis difficult.

[0016] Preferably, the carbon chain lengths of the acrylate monomer a and the acrylate monomer b are different; the carbon chain length of the acrylate monomer a is longer than the carbon chain length of the acrylate monomer b.

[0017] Furthermore, the carbon chain lengths of the epoxy-free acrylate monomer a and the epoxy-free acrylate monomer b are different; the carbon chain length of the epoxy-free acrylate monomer a is longer than the carbon chain length of the epoxy-free acrylate b.

[0018] Further, the epoxy-free acrylate monomer a is selected from one or more of n-hexyl acrylate, n-hexyl methacrylate, n-octyl acrylate, n-octyl methacrylate, n-nonyl acrylate, n-nonyl methacrylate, isooctyl acrylate, isooctyl methacrylate, isononyl acrylate, isononyl methacrylate, n-decyl acrylate, n-decyl methacrylate, isodecyl acrylate, isodecyl methacrylate, n-undecyl acrylate, n-undecyl methacrylate, isodecyl acrylate, isodecyl methacrylate, n-dodecyl acrylate, n-dodecyl methacrylate, isododecyl acrylate, and isododecyl methacrylate; further, the epoxy-free acrylate monomer a is n-hexyl acrylate.

[0019] Preferably, the epoxy-free acrylate monomer b is selected from one or more of methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, n-propyl acrylate, n-propyl methacrylate, n-butyl acrylate, n-butyl methacrylate, isobutyl acrylate, and isobutyl methacrylate; further, the epoxy-free acrylate monomer b is ethyl acrylate.

[0020] Preferably, the epoxy-containing acrylate monomer d is selected from glycidyl methacrylate or glycidyl acrylate.

[0021] The applicant has found that when the epoxy-containing acrylate monomer d in the acrylic copolymer A is selected from glycidyl methacrylate or glycidyl acrylate, the heat resistance of the pure glue adhesive can be improved, and the pure glue adhesive can be provided with good chemical corrosion resistance and moisture resistance. The possible reason is that in the present invention, the epoxy group in the epoxy-containing acrylate monomer d can provide a crosslinking site for the acrylic copolymer A, and when the epoxy-containing acrylate monomer d is selected from glycidyl methacrylate or glycidyl acrylate, because of its short carbon chain, its active vinyl and epoxy groups can provide better reaction activity, so that the cured product of the pure glue adhesive forms a three-dimensional crosslinking structure, thereby improving the heat resistance of the pure glue adhesive, and good chemical corrosion resistance and moisture resistance.

[0022] Furthermore, the epoxy-containing acrylate monomer d is glycidyl methacrylate.

[0023] In the present invention, the acrylic copolymer A can be prepared by any conventional copolymerization method.

[0024] Preferably, the weight average molecular weight of the acrylic copolymer A is 100,000-300,000.

[0025] Furthermore, the weight average molecular weight of the acrylic copolymer A is 150,000-250,000.

[0026] The applicant has found that controlling the molecular weight of the acrylic copolymer A can promote the stability of the adhesive force. When the molecular weight of the acrylic copolymer A is too small, the heat resistance and adhesive force of the pure adhesive are reduced. When the molecular weight is too large, the molecular weight difference of each molecule is too large, and there is a large difference in the intermolecular force of each molecule. When the acrylic copolymer reacts with the epoxy resin to prepare the adhesive, the adhesive is prone to cohesive force oscillation, the adhesive force is unstable, and the viscosity of the copolymer solution is too large, making it difficult to apply the pure adhesive.

[0027] Preferably, the epoxy-free acrylate monomer a, the epoxy-free acrylate monomer b and the epoxy-containing acrylate monomer d are all monomers that do not contain a free carboxyl group.

[0028] Preferably, the epoxy resin B is a bisphenol A type epoxy resin; and the epoxy resin C is a glycidyl ester type epoxy resin.

[0029] Furthermore, the bisphenol A type epoxy resin model is epikote 828, purchased from Hansen; the glycidyl ester type epoxy resin model is E-58, purchased from Huisheng Electronics.

[0030] In the present invention, bisphenol A type epoxy resin is a general epoxy resin, which is industrially mature, does not produce small molecular volatiles during curing, has good heat resistance, and can provide good adhesion. Glycidyl ester type epoxy resin has high reaction activity, good low temperature resistance, weather resistance, and good compatibility with epoxy resin B.

[0031] Preferably, the epoxy equivalents of the epoxy resin B and the epoxy resin C are 100-1000 respectively; further, the epoxy equivalents are 100-400.

[0032] When the epoxy equivalent is less than 100, the reaction activity is low, resulting in low adhesion of the pure glue adhesive and poor heat resistance; when the epoxy equivalent is greater than 1000, the flexibility of the pure glue adhesive is poor, resulting in cohesive force oscillation and unstable adhesion.

[0033] Preferably, the epoxy resin curing agent D is an acid anhydride curing agent; further, the acid anhydride curing agent is selected from one or more of phthalic anhydride, methyltetrahydrophthalic anhydride, trimellitic anhydride, endomethylenetetrahydrophthalic anhydride, tetrahydrophthalic anhydride, benzophenonetetracarboxylic dianhydride, and pyromellitic dianhydride; further, the acid anhydride curing agent is methyltetrahydrophthalic anhydride.

[0034] Preferably, the crosslinking agent E is a chain amine crosslinking agent; further, the crosslinking agent E is a polyamine structure with a carbon atom number ≥ six; further, the crosslinking agent E is 1,6-hexanediamine.

[0035] In the present invention, the crosslinking agent E is a chain amine crosslinking agent. As a chain structure, it can provide flexibility to the pure rubber adhesive. The amino group serves as a crosslinking point to provide active hydrogen to crosslink with the acrylic copolymer to form a three-dimensional network structure, thereby improving the heat resistance and adhesion of the pure rubber adhesive.

[0036] Preferably, the raw materials for preparing the acrylic pure glue include, by weight, 100 parts of acrylic copolymer A, 10-30 parts of epoxy resin B, 5-15 parts of epoxy resin C, 0.2-3 parts of crosslinking agent E, 6-25 parts of epoxy resin curing agent D, and 30-50 parts of new flame retardant filler F.

[0037] Furthermore, it comprises 100 parts of acrylic copolymer A, 15-25 parts of epoxy resin B, 8-12 parts of epoxy resin C, 0.6-1.5 parts of crosslinking agent E, 8-15 parts of epoxy resin D, and 35-45 parts of novel flame retardant filler F.

[0038] In the present invention, too little epoxy resin B will reduce the heat resistance of the adhesive, and too much epoxy resin C will reduce the weather resistance of the adhesive, and too much epoxy resin C will reduce the adhesive strength.

[0039] If the amount of epoxy resin curing agent D is too little, the epoxy resin cross-linking degree is insufficient, and the heat resistance and adhesion are reduced; if the amount of curing agent is too much, there will be curing agent residue, and the heat resistance of the pure glue adhesive will be reduced;

[0040] If the amount of crosslinking agent E is too little, the crosslinking degree of the acrylic copolymer is insufficient, and the amount of glue overflow is large. If the amount is too much, the crosslinking agent will remain, and the heat resistance and bonding strength of the pure glue adhesive will be reduced;

[0041] If the amount of the new flame retardant filler F is too small, the vibration of the cohesive force of the pure glue cannot be improved, and the flame retardant performance cannot reach the 94VTM-0 level. If the amount is too large, the bonding strength of the pure glue adhesive will be reduced.

[0042] Beneficial Effects

[0043] 1. The technical solution provided by the present invention can improve the difficulty of material synthesis of acrylic pure glue adhesives, reduce the weight average molecular weight of acrylic copolymers without changing the bonding strength, reduce energy consumption, save costs, and at the same time improve the cohesive force oscillation of acrylic pure glue adhesives and improve the stability of bonding performance.

[0044] 2. The present invention provides a halogen-free thermosetting composition with high flame retardancy, the flame retardancy of which can reach 94VTM-0 level, and has excellent heat resistance, dimensional stability, flexibility, folding resistance and processing performance.

[0045] 3. As a method for improving the molecular weight problem of acrylic pure adhesive materials, the present invention uses a specific chain amine crosslinking agent to increase the crosslinking degree of acrylic copolymers, thereby improving the heat resistance and adhesion of the materials.

[0046] 4. As a method for improving the bonding stability of acrylic pure glue adhesives, the present invention uses a new type of phosphorus-containing complex to complex with acrylic pure glue to improve the cohesive force oscillation of the adhesive and achieve the purpose of stabilizing the bonding strength of the pure glue.

[0047] 5. The pure acrylic adhesive provided by the present invention has good and stable adhesion to metal plates such as polyimide film, copper foil, epoxy glass fiber board, stainless steel, etc., and has good storage properties at room temperature and excellent flame retardant properties. DETAILED DESCRIPTION

[0048] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The experimental methods in the examples without specifying specific conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without specifying the manufacturer are all conventional products that can be purchased commercially.

[0049] Examples 1-9, Comparative Examples 1-9

[0050] Embodiments 1 to 9 of the present invention and Comparative Examples 1 to 9 provide a kind of pure acrylic glue, and the components are shown in Table 1 and Table 2 respectively in parts by weight.

[0051] A method for preparing pure acrylic glue is provided, and all components are mixed evenly to obtain the glue.

[0052] Performance Testing

[0053] The adhesive prepared in Examples 1 to 9 and Comparative Examples 1 to 9 of the present invention is applied on the substrate film using a roller coater or a rod coater to form a uniform coating, and is dried at 60 to 135° C. to obtain a dry thickness of 10 to 150 μm. Another layer of substrate protective film is attached to the dried adhesive layer.

[0054] 1. Peel strength test

[0055] Remove one side of the substrate film and transfer it to the polyimide film, peel off the other side of the substrate film and transfer it to the copper foil (not limited to copper foil, it can be attached to stainless steel plate, glass fiber board, polyimide film and other substrates), and quickly press the polyimide film-pure glue adhesive-copper foil structure at 160-180℃ / 100kgf / 120s, and put it in a 140℃-160℃ oven for curing (or press at 140℃-180℃ for one hour).

[0056] The cured structure was subjected to a 90-degree peel test at a peeling speed of 50 mm / min to measure the force required for peeling. The results are shown in Tables 1 and 2.

[0057] 2. Flame retardant performance test

[0058] According to the UL 94 vertical burning method, the test results are shown in Table 1 and Table 2.

[0059] Table 1

[0060]

[0061]

[0062] Table 2

[0063]

[0064] It can be seen from the test data in Table 1 and Table 2 that the average peel strength of Examples 1-9 is above 26 N / cm, and the flame retardant properties thereof have reached the V-0 level.

[0065] The weight average molecular weight of the acrylic copolymer in comparative example 1 is 500,000, the molecular weight difference of each molecule is too large, and there is a large difference in the intermolecular force of each molecule. When the acrylic copolymer is reacted with the epoxy resin to prepare an adhesive, the adhesive produces cohesive force oscillations, resulting in unstable bonding force.

[0066] In the monomers for synthesizing the acrylic copolymer in Comparative Example 2, the proportion of the epoxy-free acrylate monomer (a) and the epoxy-free acrylate monomer (b) is too small, while the proportion of the acrylonitrile monomer (c) and the epoxy-containing acrylate monomer (d) is too large, resulting in insufficient flexibility, cohesive force oscillation in the bonding force and low bonding force.

[0067] The pure glue adhesive in Comparative Example 3 contains too much bisphenol A epoxy resin, which results in decreased bonding strength and easily reduces the room temperature storage stability of the adhesive.

[0068] In Comparative Example 4, the pure glue adhesive has too much curing agent, and some remain unreacted, resulting in reduced bonding strength.

[0069] The pure glue adhesive in Comparative Example 5 uses too much cross-linking agent, which leaves residues, resulting in reduced adhesion and easily reducing the room temperature storage stability of the adhesive.

[0070] Comparative Example 6 did not add the novel filler complex aluminum diethylphosphinate, and its cohesive force oscillation could not be improved, and its adhesive force was unstable.

[0071] Comparative Examples 7-8 use fillers aluminum hydroxide and calcium carbonate to replace the new filler complex aluminum diethylphosphinate, respectively, but the cohesive force fluctuations cannot be improved and the bonding force is unstable.

[0072] In Comparative Example 9, the amount of the novel filler complex aluminum diethylphosphinate used was reduced, and the cohesion of the adhesive could not be completely improved, resulting in unstable bonding strength, but the degree of fluctuation was significantly reduced; its flame retardant performance was also reduced.

Claims

1. A pure acrylic glue, characterized in that: The raw materials for preparing the acrylic pure glue include, by weight, 100 parts of acrylic copolymer A, 10-30 parts of epoxy resin B, 5-15 parts of epoxy resin C, 0.2-3 parts of crosslinking agent E, 6-25 parts of epoxy resin curing agent D, and 30-50 parts of new flame retardant filler F; the new flame retardant filler F is a phosphorus-containing flame retardant complex having an average particle size of 3 to 10 μm; the phosphorus-containing flame retardant complex is aluminum diethylphosphinate; The raw materials of the acrylic copolymer A include, by weight percentage, 30-50% of an acrylate monomer a not containing epoxy groups, 10-30% of an acrylate monomer b not containing epoxy groups, 10-30% of an acrylonitrile monomer c, and 1-10% of an acrylate monomer d containing epoxy groups; The carbon chain lengths of the epoxy-free acrylate monomer a and the epoxy-free acrylate monomer b are different; the carbon chain length of the epoxy-free acrylate monomer a is longer than the carbon chain length of the epoxy-free acrylate b; The epoxy-free acrylate monomer a is n-hexyl acrylate, the epoxy-free acrylate monomer b is ethyl acrylate; the epoxy-containing acrylate monomer d is glycidyl methacrylate; The weight average molecular weight of the acrylic copolymer A is 150,000-250,000.

2. The acrylic ester pure glue according to claim 1, characterized in that: The epoxy resin B is a bisphenol A type epoxy resin; the epoxy resin C is a glycidyl ester type epoxy resin.

3. The acrylic ester pure glue according to claim 1, characterized in that: The epoxy resin curing agent D is an acid anhydride curing agent.

4. The acrylic ester pure glue as claimed in claim 1, characterized in that: The crosslinking agent E is a chain amine crosslinking agent.

Citation Information

Patent Citations

  • Acrylic adhesive composition and acrylic adhesive sheet

    CN1754933A

  • Flame retardant adhesive composition, and adhesive sheet, coverlay film and flexible copper-clad laminate using same

    CN101157838A

  • Heat-curing resin composition, heat-curing adhesive sheet, and method for producing heat-<wbr / >curing adhesive sheet

    CN103221449A